Heterogeneity, Vetoes, and Exit Clauses in Federal Systems - Martijn Huysmans (Center for Economic Studies and ifo Institute (CESifo), 2018)
The vast majority of federations lack exit clauses. Existing theoretical explanations of this stylized fact focus on issues of credible commitment, signaling, and the risk of strategic exploitation. However, such accounts are unable to explain the adoption by the European Union (EU) of Article 50, which allows withdrawal. I contend and demonstrate empirically that in the case of the EU, an exit-voice logic lies at the basis of Article 50. More generally, in heterogeneous (quasi-)federations formed through voluntary accession, prospective members may require an exit right in order to join, especially if they will not have a veto against policy changes. This hypothesis is borne out empirically by a probit regression on the positions of 94 delegates at the European Convention, which shows that heterogeneity drove support for an exit right.
Keywords: D70; H77; P48; 330; exit; withdrawal; secession; federalism; European Union